Not Just Hocus POCUS: Implementation of a Point of Care Ultrasound Curriculum for Internal Medicine Trainees at a Large Residency Program. Issue 11 (24th May 2019) - Mellor, Thomas E; Junga, Zachary; Ordway, Sarah; Hunter, Timothy; Shimeall, William T; Krajnik, Sarah; Tibbs, Lisa; Mikita, Jeffrey; Zeman, Joseph; Clark, Paul
Abstract: Introduction: In 2018, the American College of Physicians formally acknowledged the importance of Point of Care Ultrasound (POCUS) to the practice of internal medicine (IM). For the military internist, POCUS training is critical for care of the trauma patient in austere environments, mass casualty events and natural disasters. While emergency medicine and critical care training programs have adopted POCUS education, few IM programs have integrated POCUS into their core curricula. We designed and implemented an iterative POCUS curriculum for trainees at a large military IM residency program over a two-year period. Methods: In collaboration with our critical care and simulation departments, we developed a pilot curriculum consisting of five, 60-minute courses offered on a voluntary basis at monthly intervals throughout 2017. Based on the pilot's success we incorporated a POCUS curriculum into the core academics received by all IM trainees during the 2017–2018 academic year. Trainees attended seven, 3-hour sessions during their scheduled academic time taught by subspecialists with POCUS expertise in an on-site simulation center. Baseline surveys and knowledge assessment examinations were administered during orientation and repeated at the end of the academic year. Comparison of results before and after the POCUS curriculum was the primary outcome evaluated. Results: Intervention #1: Pilot, 2016 – 2017 Academic Year 45 trainees attended at least one course with an average of 1.8 sessions per trainee. Baseline survey data showed 91% of trainees believe POCUS is quite or extremely beneficial for their patients, but 73% feel slightly or not at all confident in POCUS knowledge. The pre-test mean and median scores were 71% and 77% respectively, which both increased to a post-test mean and median of 81%. Post-test mean percentage correct for trainees attending 1, 2, or 3 courses was 74%, 82%, and 91% respectively. Intervention #2: Incorporation of POCUS into Core Academics, 2017 – 2018 Academic Year All 75 trainees participated in training with an average of 3.77 sessions attended per trainee. Survey analysis revealed significant improvement in confidence of performing ultrasound-guided procedures ( p = 0.0139), and a 37% absolute increase in respondents who anticipate using ultrasound in their clinical practice ( p = 0.0003). The mean pre-test score was 67.8% with median of 63.6% while mean and median post-test scores were 82.1% and 81.8%, with an absolute improvement of 14.3% and 18.2% respectively ( p = 0.0004). Conclusion: A structured POCUS curriculum was successfully incorporated at a large multiservice military IM residency program, with demonstrated retention of knowledge, improved confidence in performance of ultrasound guided invasive procedures, and increased interest in the use of POCUS in future clinical practice. Similar programs should be implemented across all IM programs in military graduate medical education to enhance operational readiness and battlefield care.